2020
DOI: 10.31234/osf.io/7m586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What you see is what you hear: Twenty years of research using the Sound-Induced Flash Illusion

Abstract: In the Sound-Induced Flash Illusion (SIFI) sound dramatically alters visual perception, as presenting a single flash with two beeps results in the perception of two flashes. In this timely review, we synthesise 20 years of research using the SIFI, from over 100 studies. We discuss the neural and computational principles governing this illusion and examine the influence of perceptual experience, development, ageing and clinical conditions. Convergent findings show that the SIFI results from optimal integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 180 publications
1
21
0
Order By: Relevance
“…In addition, a number of studies have shown agerelated changes in multisensory integration and perception (Murray et al, 2016;Hirst et al, 2018Hirst et al, , 2020. Overall, these studies indicate that multisensory integration is plastic and dynamic across development from early life to adulthood.…”
Section: Clinical Applications and Future Directionsmentioning
confidence: 85%
“…In addition, a number of studies have shown agerelated changes in multisensory integration and perception (Murray et al, 2016;Hirst et al, 2018Hirst et al, , 2020. Overall, these studies indicate that multisensory integration is plastic and dynamic across development from early life to adulthood.…”
Section: Clinical Applications and Future Directionsmentioning
confidence: 85%
“…Keil (2020) also summarized the neural mechanisms underlying the illusion. Hirst et al. (2020) also published a review covering 20 years of literature, and the review not only summarized the theoretical models that explained the SiFI but also summarized the findings of electroencephalography and functional magnetic resonance imaging.…”
mentioning
confidence: 99%
“…Andersen et al, 2004;Takeshima & Gyoba, 2013;Pérez-Bellido et al, 2015) and between (e.g. Foss-Feig et al, 2010;Setti et al, 2011;McGovern et al, 2014;Stevenson et al, 2014;Noel et al, 2016) groups (as reviewed in Hirst et al, 2020). Furthermore, it has also been demonstrated that the properties of the temporal binding window associated with the SIFI can change in the same individuals following a period of perceptual training (Setti et al, 2014;McGovern et al, in prep), while other studies show that the magnitude of the SIFI is modulated by expertise (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ernst & Banks, 2002;Alais & Burr, 2004;Shams et al, 2005). Since its discovery over 20 years ago, the SIFI has been employed as a useful means to assess the nature of multisensory perception in humans and has helped to reveal, amongst other things, the influences of perceptual experience, ageing and a variety of clinical conditions on multisensory integration (see Hirst et al, 2020 andKeil, 2020 for recent reviews).…”
Section: Introductionmentioning
confidence: 99%